The load-bearing capacity of timber-glass composite I-beams made with polyurethane adhesives = Nośność belek drewniano-szklanych zespolonych przy udziale klejów poliuretnaowych - Rodacki, Konrad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article discusses the issue of composite timber-glass I-beams, which are an interesting alternative for load-bearing beams of ceilings and roofs. The reasoning behind the use of timber-glass I-beams is the combination of the best features of both materials - this enables the creation of particularly safe beams with regard to structural stability and post-breakage load capacity.
Keywords: timber-glass I-beams; polyurethane adhesive; innovative composite structures; composite structures; belka drewniano-szklana; belka zespolona; klej poliuretanowy; konstrukcje zespolone nowej generacji